2013
DOI: 10.1080/17543266.2013.845250
|View full text |Cite
|
Sign up to set email alerts
|

Design functions in transformable garments for sustainability

Abstract: This study was designed as a bottom-up approach to understanding what kind of changeable functions people desire in transformable garments by analysing a wardrobe database, participants' perceptions of garment varieties, and participants' values related to transformable garments (specifically tops, the wardrobe garment with the most observed design variability). The wardrobe database was analysed using data quantification and descriptive analysis. Style-conscious professional women, ages 20-40, were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…The need for novelty and newness has driven consumers to purchase new apparel products frequently and to dispose of a diverse amount of garments that are underutilized. Approximately, only about 38% of young consumers' wardrobes are regularly worn (Koo et al 2014). More specifically, fast fashion speeds up consumer's acquisition and makes it possible for consumers to obtain more styles with lower quality and at lower cost (Cao et al 2014), which, in turn, increases landfill waste.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The need for novelty and newness has driven consumers to purchase new apparel products frequently and to dispose of a diverse amount of garments that are underutilized. Approximately, only about 38% of young consumers' wardrobes are regularly worn (Koo et al 2014). More specifically, fast fashion speeds up consumer's acquisition and makes it possible for consumers to obtain more styles with lower quality and at lower cost (Cao et al 2014), which, in turn, increases landfill waste.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers' demands have been diversifying, which makes it harder to predict due to rapidly changing trends and fashion tastes (Kang and Park-Poaps 2010). Being transformable allows the aesthetics and functionality of the items to be converted into multiple styles and functions to meet consumers' need for novelty and versatility (Koo et al 2014;Rahman and Gong 2016). This trend is expected to increase the use intensity, extend the lifespan of apparel products, and reduce disposal (Koo et al 2014), which may be a potential solution to the problem of excessive apparel consumption faced by the fashion industry today.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recent study conducted by Koo, Dunne, and Bye (2014), many individuals use 6-38% of their wardrobe on a regular basis. In the same vein, McGrath (2012) reported that her respondents use about 50% of their wardrobe.…”
Section: Clothing Relevancy and Longevitymentioning
confidence: 99%